The Influence of Perceived Product Quality and Price, Service Quality on Intention to Repeat Treatment with Green Products as a Moderator Variable - Chandra, Bobby; Mulyowahyudi, Alugoro (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the influence of perceived product quality, price and service quality on intention to repeat treatment at beauty clinics in Jakarta, with green products as a moderator variable. The phenomenon of increasing awareness of health and environmental sustainability has given rise to a trend of using green products in various sectors, including the beauty industry. However, there is still not much research that comprehensively examines how preferences for green products influence consumers' decisions to return to treatment. The population of this study are consumers who have had treatment and have the intention to repeat treatment at beauty clinics in Jakarta. Research samples will be taken from five beauty clinics located in Jakarta. Respondent criteria include consumers who have undergone treatment at the clinic and are willing to participate in the research. Data will be collected through a questionnaire, then analyzed using SEM-PLS. The research results show that perceived product quality, perceived price, and service quality have a significant positive effect on intention to repeat treatment. Furthermore, green products were found to moderate the relationship between perceived product quality and intention to repeat treatment in a significant negative direction, conversely, green products moderated the relationship between perceived price and service quality and intention to repeat treatment in a significant positive direction